Finite Element Analysis Applications in Mechanical Engineering - Ebrahimi, Farzad (IntechOpen, 2012)
In the past few decades, the Finite Element Analysis (FEA) has been developed into a key indispensable technology in the modeling and simulation of various engineering systems. The present book is a result of contributions of experts from international scientific community and collects original and innovative research studies on recent applications of FEA in five major topics of mechanical engineering namely, fluid mechanics and heat transfer, machine elements analysis and design, machining and product design, wave propagation and failure-analysis and structural mechanics and composite materials. It is meant to provide a small but valuable sample of contemporary research activities around the world in this field and it is expected to be useful to a large number of researchers. The introductions, data, and references in this book will help the readers know more about this topic and help them explore this exciting and fast-evolving field.